Strengthening Integrated Services Through Website-Based Applications in Welcoming PTN-BH Universitas Negeri Semarang (Educational Management, 2022)
In accordance with current technological developments, the development of a service system has led to the use of website-based information technology, where all information in the system can be displayed using Internet media. For Integrated services implemented at the Faculty of Law it is based on Law Number 14 of 2008 concerning Public Information Disclosure, Law Number 25 of 2009 concerning Public Services, and Presidential Regulation Number 97 of 2014 concerning One-Stop Integrated Implementation. That the common thread between the KIP Law and the Public Service Law is an effort to increase public participation and participation in public policies. The poor performance of public services so far is partly due to the lack of transparency in the implementation of public services (Eko Noer Kristiyanto, 2016). This research aims to make it easier for stakeholders to get fast, easy and transparent services, improve the quality and quantity of services, integrate service systems by providing added value to increase benefits, speed up services and facilitate coordination, all series of services can be monitored properly. The method used in this research is descriptive qualitative research. The results of the research on the SI-LAW Service System, Faculty of Law, Semarang State University, were built using the SI-Law Service System using PHP and the MySQL database version 7.4.32 with the codeigniter framework facilitated by the Information and Communication Technology Technical Implementation Unit (UPT ICT) UNNES. In increasing the strengthening of public services through a website-based system, overall respondents rate above 50%, which means that the service has been received and is running well. There is a value that is below 50%, namely the service complaint element which still has the lowest score (44.8%), namely the complaint service element is still considered not fast enough, so it needs to be continuously improved so that the complaint service is in accordance with procedures and is handled quickly.